Vertical characteristics of radar reflectivity and DSD parameters in intense convective clouds over South East South Asia during the Indian Summer monsoon: GPM observations - Kumar S. (2019)
Global precipitation measurement (GPM) launched in February 2014 as a legacy of Tropical Rainfall Measuring Mission (TRMM). Both satellites carry precipitation radar (PR), which measures the three-dimension structure of precipitation from space. Compared to TRMM PR, GPM has dual-polarized radar (DPR) and provides the raindrop size distribution (DSD) including mass-weighted mean diameter (Dm, in mm) and normalized DSD scaling parameter for concentration (Nw, in mm–1 m–3) (DSD parameters), along with radar reflectivity factor (Ze) from the surface to 21.875 km. Here we investigated the regional differences in intense convective clouds over South East & South Asia (SESA) and explored the differences in the East and West coast of India, by selecting the various areas. We defined two types of clouds, namely Cumulonimbus towers (CbTs) and intense convective clouds (ICCs) based on the Ze and height thresholds. CbTs must consist of 20 dBZ at 12 km, with echo base height less than 3 km, where ICCs are classified based on Ze threshold at 8 km (ICC8) and 3 km (ICC3). The average vertical profiles of CbTs indicate a strong west to east gradient, as the west side/coast of India has intense CbTs, with higher hydrometeors size, and decreases at east side/coast of India. The results reveal that the western side of India (Western Himalaya Foothills and Western Ghats) consists of fewer CbTs, but they are more intense. ICC3s are distributed nearly uniformly over the SESA but show the regional differences in Ze and DSD parameters in the vertical profiles. Despite various height and Ze thresholds used in the present study, WHF has the strongest vertical profile for all type of cloud cells, and indicate the importance of specific features and orographic modulated flow. The hydrometeors size is highest over Western Himalaya Foothills and least over the Bay of Bengal. Hydrometeors concentration shows the north-south gradient and higher over oceanic areas. Two coastal areas, Western Ghats and Myanmar show the different characteristics. Western Ghats CbTs are more intense, with higher hydrometeors size, whereas Myanmar has weaker convection and consists of small-sized hydrometeors. Hydrometeors size and concentration show the opposite characteristics, as hydrometeors size is higher for intense average Ze profiles, whereas hydrometeors concentration is less for intense average Ze profiles. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.